Peran Manajemen dalam Menunjang Keberlangsungan Bisnis Startup Di Indonesia: Studi Berdasarkan Data Sekunder - Ropik Tri Wianto; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
The growth of startup businesses in Indonesia has accelerated significantly in recent years, driven by technological advancement, digitalization, and substantial potential. According to the book Bisnis Proyek IT Mastery - Siapapun Bisa Berbisnis Digital (2022) by Yusef Maulana and an article from Kompas.com (2023), this rapid development is also accompanied by a high failure rate among startups. The main causes of failure include poor planning, weak organization, ineffective leadership, operational mismanagement, and a lack of sustainable innovation. This study adopts a qualitative approach through a literature review and secondary data analysis sourced from Kompas.com articles, CB Insights reports, and various academic journals. The findings indicate that the primary reasons for failure are closely related to the suboptimal implementation of management functions. Therefore, effective management becomes a crucial key in determining the success of a startup. With proper management, startups can better plan strategies, organize human resources, and manage risks more efficiently.